Physiotherapy services in patient care in Bhutan - Monu Tamang; Thinley Dorji (BMC, 2021)
Abstract Physiotherapy and rehabilitative services are an integral part of patient care, but in many developing countries they are not considered a priority and are either not available or not easily accessible to those who need them. Bhutan is one such country where healthcare is provided free of cost to all, but as of 2021 physiotherapy services were available only in 26 of 48 hospitals and 19 of 20 districts. The number of physiotherapy professionals per 10,000 population is 1.4 with significant rates of attrition. There is lack of awareness among patients and other health professionals about physiotherapy and rehabilitation services. The country needs to integrate physiotherapy and rehabilitation services into the overall health policy framework and develop proper planning of human resources and infrastructure to meet the current and future demands.